ГЕОГРАФИЯ И ТЕНДЕНЦИИ ПРЕСТУПНОГО НЕДРОПОЛЬЗОВАНИЯ В ОБЩЕМИРОВОМ ИЗМЕРЕНИИ - Максименцев, Максим Геннадиевич (SUPREMANCE OF LAW, 2019)
The article is focused on studying the geography and tendencies of criminal subsoil use within the global dimension. It has been established that the regions with the highest criminal activity in this area are: Africa (Democratic Republic of the Congo, Ghana, Libya, Tanzania, Nigeria, Somalia, etc.), Latin America (Venezuela, Colombia, Peru, Chile, etc.), South- East Asia (Mekong area), Middle East region (Syria, Iraq, etc.). The author has noted on the escalation, administered stimulation of military and political tension in the regions of concentration of mineral resources deposits in the corresponding territories of the “Third World” countries. Funds obtained from the illegal extraction of mineral resources are often used to finance terrorism, the activities of illegal armed groups.